Notes on the accumulation and utilization of capital: Some empirical issues - Michalis Nikiforos (Levy Economics Institute of Bard College, 2020)
The paper makes three contributions. First, following up on Nikiforos (2016), it provides an in-depth examination of the Federal Reserve measure of capacity utilization and shows that it is closer to a cyclical indicator than a measure of long run variations of normal utilization. Other measures, such as the average workweek of capital or the national emergency utilization rate are more appropriate for examining long-run changes in utilization. Second, and related to that, it argues that a relatively stationary measure of utilization is not consistent with any theory of the determination of utilization. Third, based on data on the lifetime of fixed assets it shows that for the issues around the “utilization controversy” the long run is a period after thirty years or more. This makes it a Platonic Idea for some economic problems.
Keywords: B22; O4; D3; D2; 330; Accumulation; Growth; Distribution; Utilization